PENGUJIAN VIABILITAS DAN VIGOR DARI TIGA JENIS KACANG- KACANGAN YANG BEREDAR DI PASARAN DAERAH SAMARANG, GARUT - Isna Tustiyani; Rama Adi Pratama; Dadi Nurdiana (Jurnal Agroekoteknologi, 2016)
The aim of this research was to study the viability and vigor of soybean, peanut, and greenbean seeds sold on the market area of Samarang, Garut. The experiment was conducted at the Integrated Agricultural Laboratory, Faculty of Agriculture, University of Garut from December 2015 to January 2016 using Randomized Complete Design Group with three treatments i.e. types of nuts (soybeans, peanuts and green beans). The experimental results showed that the types of nuts sold in Samarang, Garut significantly affect vigor in the sand testing methods. The Soybean had lower vigor than peanuts and green beans. The nuts that sold in Samarang, Garut had no significant affect on water content and germination rate.Keywords: Green beans, Peanuts, Soybeans, Ukddp, Uak